Climate-induced shifts in sulfate dynamics regulate anaerobic methane oxidation in a coastal wetland - Lee, Jaehyun; Yang, Yerang; Kang, Hojeong; Noyce, Genevieve L.; Megonigal, J. Patrick (American Association for the Advancement of Science, 2025)
Anaerobic methane oxidation (AMO) is a key microbial pathway that mitigates methane emissions in coastal wetlands, but the response of AMO to changing global climate remains poorly understood. Here, we assessed the response of AMO to climate change in a brackish coastal wetland using a 5-year field manipulation of warming and elevated carbon dioxide (eCO2). Sulfate (SO42-)-dependent AMO (S-DAMO) was the predominant AMO process at our study site due to tidal inputs of SO42-. However, SO42- dynamics responded differently to the treatments; warming reduced SO42- concentration by enhancing SO42- reduction, while eCO2 increased SO42- concentration by enhancing SO42- regeneration. S-DAMO rates mirrored these trends, with warming decreasing S-DAMO rates and eCO2 stimulating them. These findings underscore the potential of climate change to alter soil AMO activities through changing SO42- dynamics, highlighting the need to incorporate these processes in predictive models for more accurate representations of coastal wetland methane dynamics.